Self‐regulatory control processes in youths: A temporal network analysis approach - Fiorella Turri; Andrew Jones; Lauriane Constanty; Setareh Ranjbar; Konstantin Drexl; Giorgia Miano; Caroline Lepage; Kerstin Jessica Plessen; Sébastien Urben (Wiley, 2024)
Abstract Objective This study aimed to better understand the temporal interrelationships among self‐control, response inhibition, and anger (i.e., momentary state and rumination) on both the within‐ and between‐person levels in male adolescents. Method We applied temporal network analyses among 62 male adolescents with a wide range of behavioral difficulties. Self‐control, momentary anger, and anger rumination were mapped by self‐report measures, whereas we measured response inhibition through an ambulatory Go/No‐go task (two measures a day-morning and afternoon-over a 9‐day period). Results Temporal network analysis, at the within‐person level, revealed that morning measures of response inhibition, anger rumination, and self‐control were related to the corresponding measure in the afternoon. More efficient response inhibition in the morning was associated with higher self‐control in the afternoon. Higher anger rumination in the morning led to higher momentary anger in the afternoon. In a concurrent within‐person network, higher momentary anger was reciprocally associated with lower self‐control. At the between‐person level, higher momentary anger was correlated to higher anger rumination, lower response inhibition, and lower self‐control. Discussion This study provides insight into the dynamic interactions among self‐control, response inhibition, and anger (momentary state and rumination) in male adolescents, advancing the understanding of self‐regulatory control functioning.